In vivo treatment with the casein kinase 2 inhibitor 4, 5, 6, 7‐tetrabromotriazole augments the slow afterhyperpolarizing potential and prevents acute epileptiform activity. Issue 1 (6th December 2013) - Brehme, Hannes; Kirschstein, Timo; Schulz, Robert; Köhling, Rüdiger
Summary Objective The slow afterhyperpolarizing potential (sAHP) following prolonged depolarization is a major intrinsic mechanism of neuronal inhibition, by powerfully dampening excitability for up to 2 s. Therefore, an altered sAHP function might be vulnerable to hyperexcitable states such as epilepsy. Here, we have investigated the role of casein kinase 2 (CK2) on the sAHP in control and chronically epileptic tissue. Methods Using the rat pilocarpine model of chronic temporal lobe epilepsy, we performed whole‐cell patch‐clamp recordings of acutely isolated CA1 pyramidal cells and field potential measurements on hippocampal slices. Results Chronic oral administration of the CK2 inhibitor 4, 5, 6, 7‐tetrabromotriazole (TBB) for 4 days prior to brain dissection caused a significant increase of the sAHP‐mediating current in both control and epileptic tissues. In contrast, when TBB was acutely applied during the patch‐clamp recording, the sAHP remained unaltered, indicating that chronic CK2 inhibition was required for sAHP augmentation. To test whether CK2 inhibition also has an anticonvulsive effect, we evoked recurrent epileptiform discharges (REDs) in hippocampal slice preparations by Mg2+ removal. It is important to note that chronic oral TBB administration abolished REDs induced by 0‐Mg2+ solution, suggesting that CK2 inhibition indeed has anticonvulsive and perhaps antiepileptogenic properties. Significance Our data demonstrated that CK2 inhibition augments the sAHP and might represent a novel mechanism of action of anticonvulsant drugs.